Respostas

2013-08-20T00:19:37-03:00
A=1              a+b=3
                     1+b=3
                      b= =3-1
                      b=2
a+b +c= 5 
    3 + c = 5
    c=5 - 3
    c=2

d+e=3        d+e +f =5                 e  + f  = 5  
                     3  +f = 5                 e + 2 = 5
                      f = 5 - 3                 e = 5 - 2
                      f = 2                      e = 3
d+e=3
d + 3 = 3
d = 3 - 3
d =0
então:
a=1       b=2      c=2       d=0       e=3         f=2

a.b.c + d.e.f
1.2.2   +   0.3.2
     4    +    0
resposta: o valor da expressão a.b.c + d.e.f = 4
1 5 1